Organizational Climate for Successful Aging - Zacher, Hannes; Yang, Jie (Frontiers in Psychology, 2016)
Research on successful aging at work has neglected contextual resources such as organizational climate, which refers to employees’ shared perceptions of their work environment. We introduce the construct of organizational climate for successful aging (OCSA) and examine it as a buffer of the negative relationship between employee age and focus on opportunities (i.e., beliefs about future goals and possibilities at work). Moreover, we expected that focus on opportunities, in turn, positively predicts job satisfaction, organizational commitment, and motivation to continue working after official retirement age. Data came from 649 employees working in 120 companies (Mage = 44 years, SD = 13). We controlled for organizational tenure, psychological climate for successful aging (i.e., individuals’ perceptions), and psychological and organizational age discrimination climate. Results of multilevel analyses supported our hypotheses. Overall, our findings suggest that OCSA is an important contextual resource for successful aging at work.